Applying the Theory of Planned Behavior to Analyze Household Energy-Saving Behavior - Nguyen, Quoc Nghi; Hoang, Thi Hong Loc; Mai, Van Nam (International Journal of Energy Economics and Policy, 2022)
Energy consumption in residential areas is increasing which leads to greenhouse gas emissions and environmental pollution. Household energy-saving behavioral intentions are diverse and influenced by many different factors. This study approaches the theory of planned behavior (TPB) with an integrated perspective (economic-oriented, technology-oriented, and behavior-oriented perspective) to demonstrate affecting factors to the energy-saving intention of households in Vietnam. Applying the structural equation modeling (SEM), the study has pointed out the above affecting factors include subjective norms, perceived behavioral control, perceived benefits, attitude, product quality, and energy policies. In which, the “perceived benefits” factor has the most impact on the energy-saving intention of households.